Valid publication of the name Carex henryi (Cyperaceae) from Asia - Deng, Yunfei (Phytotaxa, 2013)
Carex Linnaeus (1753: 972) is one of the largest genera of seed plants (Frodin 2004). It comprises about 2,000 species worldwide and is easily distinguished from other genera of Cyperaceae by having perigynia enclosing the nutlets (Reznicek 1990, Goetghebeur 1998, Govaerts et al. 2007, Mabberley 2008, Dai et al. 2010). There are 535 species in three subgenera and 57 sections recognized in China (Dai et al. 2010, Wang et al. 2012).